Microleakage in indirect partial restorations cemented with self-adhesive dual resin cements - Zaga Bendezú, Javier Cleto (2019)
The aim of this study is to compare in vitro the degree of marginal microleakage in pressed ceramic inlays made with two self-adhesive dual resin cements seT PP (SDI) and RelyX U200 (3M ESPE). Forty upper and lower premolars extracted for orthodontic reasons were evaluated and divided into two groups according to assigned cement (n = 20). Then, the preparation of class II type cavities, approximately 3 mm wide, was performed in the occlusal and proximal box; and 2 mm thick on the gingival floor and occlusal wall. They were indirectly restored with IPS e.max Press (Ivoclar Vivadent) ceramic pressed restorations, cemented with the types of cement studied according to the manufacturer's specifications. The specimens were kept in a jar and taken to thermocycling; then, cross sections were made to the crowns and the degree of microleakage was evaluated by means of a stereoscope. When comparing the microleakage between the seT PP cement and RelyX U200, it was concluded that there is no statistically significant association between the degree of microleakage and the type of cement (Pearson's Chi-square test; p > 0.05), and when observing the degree of microleakage of seT PP and RelyX U200 in the cementation of IPS e.max Pressed ceramic inlays. In conclusion, no significant differences were found between the two self-adhesive resinous cement. In both, non-microfiltration prevailed; however, for seT PP, microleakage was 17.5% in 1/3 of the cervical wall.